2013
DOI: 10.1186/1477-7525-11-147
|View full text |Cite
|
Sign up to set email alerts
|

Course of COPD assessment test (CAT) and clinical COPD questionnaire (CCQ) scores during recovery from exacerbations of chronic obstructive pulmonary disease

Abstract: IntroductionCOPD exacerbations have a negative impact on lung function, decrease quality of life (QoL) and increase the risk of death. The objective of this study was to assess the course of health status after an outpatient or inpatient exacerbation in patients with COPD.MethodsThis is an epidemiological, prospective, multicentre study that was conducted in 79 hospitals and primary care centres in Spain. Four hundred seventy-six COPD patients completed COPD assessment test (CAT) and Clinical COPD Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
2
44
1
2
Order By: Relevance
“…Numerous studies come in agreement with our results and concluded that the reduction in CAT-score detects early health status improvement and chest wall vibration reduces dyspnea in COPD patients. 4,6,12,23 Our results also coincide with pilot study carried out by Chakravorty et al whom reported that patients with AECOPD and mucus hypersecretion are at increased risk of declining lung function, tolerated the HFCWO treatment well, leading to improvement in CAT-score and quality of life and reduced symptoms. 7 Moreover; our result is consistent with Mahajan et al, who stated that HFCWO is well tolerated in adults hospitalized for AECOPD or acute asthma and significantly improves dyspnea, also reported that patient with AECOPD use fewer antibiotics, due to fewer respiratory infections with less hospitalization.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Numerous studies come in agreement with our results and concluded that the reduction in CAT-score detects early health status improvement and chest wall vibration reduces dyspnea in COPD patients. 4,6,12,23 Our results also coincide with pilot study carried out by Chakravorty et al whom reported that patients with AECOPD and mucus hypersecretion are at increased risk of declining lung function, tolerated the HFCWO treatment well, leading to improvement in CAT-score and quality of life and reduced symptoms. 7 Moreover; our result is consistent with Mahajan et al, who stated that HFCWO is well tolerated in adults hospitalized for AECOPD or acute asthma and significantly improves dyspnea, also reported that patient with AECOPD use fewer antibiotics, due to fewer respiratory infections with less hospitalization.…”
Section: Discussionsupporting
confidence: 78%
“…The total CAT score was calculated by summing the points of each variable, the higher scores represent worse health. [8][9][10][11][12] It was classified into four categorizes; low (< 10), medium (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), high (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and very high (> 30). (FEV1% pred = predicted amount as a percentage of the forced expiratory lung volume in one second; 6MWD = six minute walking distance; MMRC = modified medical research council dyspnea scale; BMI = body mass index.…”
Section: Copd Assessment Test (Cat)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is a validated eight-item questionnaire designed to assess and quantify the impact of COPD symptoms on patient health status 21 but it has been also shown to be a good tool in measuring severity 22 and recovery from exacerbations 23 . It also has two principal advantages in that it can be used in different clinical settings (primary care and second care) and shows no variability between languages 24 .…”
Section: Discussionmentioning
confidence: 99%